2017
DOI: 10.31018/jans.v9i3.1442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long - term integrated nutrient management on crop yield, nutrition and soil fertility under rice-wheat system

Abstract: Long-term effect of nitrogen substitution (25 to 50%) through different organics, viz., FYM (farm yard manure), GM (green manure) and WS (wheat straw) on crop yield, nutrition and physico-chemical properties of soil was studied under rice-wheat system. The data of long term experiment revealed that maximum grain yield of 46.83 qha -1 in wheat was obtained when 100% RDF applied through mineral fertilizers after 50% N of RDF being substituted with FYM in rice. Grain yield of wheat declined under control and sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 7 publications
5
16
0
Order By: Relevance
“…The incorporation of green gram residues along with inorganic fertilizers resulted in a significant rice yield increase of 13% over IORA [31]. The highest yield of 4.68 Mg ha −1 in wheat crop was recorded when 50% N (nitrogen) of the recommended dose of fertilizer treatment was replaced with FYM in the rice crop [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of green gram residues along with inorganic fertilizers resulted in a significant rice yield increase of 13% over IORA [31]. The highest yield of 4.68 Mg ha −1 in wheat crop was recorded when 50% N (nitrogen) of the recommended dose of fertilizer treatment was replaced with FYM in the rice crop [32].…”
Section: Discussionmentioning
confidence: 99%
“…The integrated application of organic and inorganic fertilizers for 29 years reduced soil reactions by 0.22% over the application of inorganic fertilizers alone [32]. In a long-term fertilizer experiment under the RWCS, it was reported that INM reduced BD by 16.6%, whereas the application of IORA showed a reduction of 7.3% compared to the CO treatment [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the increase in soil nutrient levels may rely on the type of organic compost added to the soil. The importance of organic compost in enhancing the availability of different soil nutrients may be attributed to several reasons, including the fact that organic compost usually stimulates soil microbial activities and their biomass, thereby enhancing the release of organic nutrients, such as nitrogen and phosphorus, in the soil [18,64]; organic compost acts as a nutrient source, wherein the different inherited ions of organic composts are released into the soil during decomposition and after application in the soil [73]; organic compost can increase cation exchange capacity, which is a very important indicator for retaining nutrients and making them available to plants [25,65]; organic compost releases ions to the soil at a slow and consistent rate, which prevents ions from leaching into ground water [74]; organic compost produces organic acids that have a positive effect in reducing the pH of calcareous soil, which help in releasing phosphorus by the solubilizing action of native soil phosphorus [75,76]; the humic and fulvic acid that are released from organic compost can improve the status of nutrients in the soil by chelating them with phenol and carboxylic groups [77].…”
Section: Impacts Of Inm Treatments On Soil Chemical Propertiesmentioning
confidence: 99%
“…Basmati rice, being a long duration and late-maturing variety, ultimately causes a delay in sowing of wheat. About 40% nitrogen, 30-35% phosphorus, 80-85% potassium, and 40-50 % sulfur (S) present in vegetative parts of a plant which rice acquired during its growth period (8,9) All nutrients which are present in rice straw are lost due to burning (10). This results in severe air pollution and loss of nutrients and organic matter (11).…”
Section: Introductionmentioning
confidence: 99%